Are Bank Regulations and A Pro-cyclicality Related to Bank Provisioning in the ASEAN Plus Three Group? - Laksanakoses, Vorasamart (2011)
This study examines a pro-cyclicality effect, income smoothing effect and capital management. By using 46 commercial banks in the ASEAN Plus Three group, this study found the existence of the pro-cyclicality effect and the capital management; however, the evidence of earning management is not found in the sample data. As a result of the tightening policy of the banking supervisions, banks need to comply with the new banking regulation, to limit the restriction on the lending activities and to improve the loan loss provision policy. More important, the regression results report that banks in this region are likely to be a forward looking in lending business which is consistent with the regulatory implementation.